LANGUAGE COMPETENCE OF POLYTECHNICAL NON-ENGINEERING GRADUATES NEEDED IN THE INDUSTRY WORLD - Sri Nur Yuliyawati,; Hazma, (International Journal of Social Science, 2022)
Changes in patterns, requirements, and competition for industrial workers have caused language lectures, both Indonesian and English courses, to be encouraged to prepare graduates from polytechnic non-engineering majors to have language competencies that are in line with industry needs. For this reason, a research was conducted on "Language Competence of Graduates of the Polytechnic Non-Engineering Department Needed by the Business World and the Industrial World" which can be used as a reference for syllabus formulation and study material for language lectures. This study aims to describe the language competencies needed by the business world and the industrial world. To achieve this goal, the descriptive method is used with the data sources of this research consisting of resource persons, namely non-engineering alumni as well as the business and industrial world as well as curriculum documents of the Bandung State Polytechnic Department of Non-engineering, documents regarding KKNI, industrial competency references and language competencies. From this research, it is known that the language competencies needed by the industrial world are 1) writing competence for office administration activities: correspondence, making reports, designing activities/proposals, making agendas and meeting minutes, developing own ideas or other people's ideas; 2) speaking competence for presentations, telephone calls, communicating with relations, negotiating, and promoting; 3) the competence to read accurately, quickly and fluently to manage information, SOPs & work instructions, company rules / regulations, process data accurately, and 4) listening competence to communicate and negotiate. These competencies are in accordance with the qualifications of the KKNI level 5 and 6 which must be possessed by polytechnic D3 and D4 graduates.